An analysis of citations in the College of Science, College of Arts and Letters and College of Social Sciences and Philosophy graduate theses (2000-2004) - Meraña, Jeffrey Y.; Carcellar, Marie Desiree R. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study used citation and bibliometric analysis to examine the literature of the university through the student literature of the three major colleges and identify some of the characteristics. The 25,471 citations taken from 357 graduate theses submitted to the colleges from 2000 to 2004 were analyzed to differentiate the citation behavior of the graduate students from College of Science (CS), College of Arts and Letters (CAL) and the College of Social Sciences and Philosophy (CSSP).
The source theses examined belonged primarily to the theses collections of the University Archives, the CS Library and selected departments of CAL. The objectives of the study were to determine: 1) the most cited bibliographic format; 2) the most frequently cited titles; 3) the most frequently cited author/s and editor/s; 4) the predominant country of publication; 5) the predominant type of material; 6) the time and age distribution of the cited materials; 7) the rate of obsolescence; 8) the core journals of each department; 9) the completeness of the bibliographies; to compare the citation behavior of the graduate students by college and by departments and to design a citation index that can be used to complement the OPAC's functionality.
For CAL and CSSP, books were the most cited format which accounted for almost half of their total citations and a wide range of formats were used to satisfy majority or 80 percent of their information needs. Journals were the most cited format for CS and together with books, internet resources, theses and dissertations acquired 80 percent of the 25,471 citations. The frequently cited book titles were "Pasyon and Revolution: Popular Movements in the Phils, 1840-1910", "The Philippine Islands, 1493-1498" and "Molecular Cloning : a Laboratory Manual". The most frequently cited authors were V.S. Almario, F. L. Jocano and C. Saloma and the most frequently cited editors were B. Lumbera, P. Bhattacharya, et al. and E. H. Blair and J. Robertson. The predominant country of publication was the United States (41.05) and the predominant type of material were foreign materials (63.47) for CS, local for CAL (70.51) and none for CSSP. The publication dates ranged from 1569 to 2004 and 50 to 80 percent of the citations for the total literature were 10 to 25 years old, respectively. The values for the median ages for CS, CAL and CSSP were 9, 29 and 28 years old, respectively.
The modal year was found to range from 0 to 9 years after publication. The rate of obsolescence varied across formats and across disciplines. The number of citations to the selected formats for CS, CAL and CSSP were found to decrease at a rate of 1.87, 1.33 and 1.59 percent per annum, respectively. Using the Bradford distribution, the cited articles were divided into 5 zones and the core journals ranged from 2 to 6 journals.
The most number of incomplete bibliographies were due to the lack of the year of publication, the place of publication, article title and publisher. Among the departments with the highest percentage of incomplete citation were NIP (45.23), MSE (34.34) and DMath (34.07). This study recommends that the results be considered for the respective libraries' collection development, the citation index be used to aid in literature search and a standard manual for thesis writing be adopted for the whole university.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Bibliographic citations; Bibliometrics; Dissertations, Academic -- Philippines -- Quezon City